Examen especial a la cuenta cartera de crédito de la cooperativa de ahorro y crédito Empleados Municipales de Latacunga ltda de la provincia de Cotopaxi año 2021 - Gualpa Yanez, Katya Estefanía (2023)
The savings and credit cooperatives have carried out different procedures to control their portfolio, even so, there are inconveniences and problems in their collection, that is, delinquency, for this reason, the application of financial audit is vital to analyze the problems found, this with the purpose of recovering the loans issued in the estimated time of collection; The execution of the integration project was carried out in the Cooperativa de Ahorro y Crédito Empleados Municipales de Latacunga Ltda.,